Contribution of ICT to Logistics Management of Fish-Exporting Companies - Franco-Medranda, Yandri Javier (2023)
This study examines the role of Information and Communication Technologies (ICT) in the logistics management of fish-exporting companies across three significant cantons in the province of Manabí, Ecuador. The purpose of this research is to identify the benefits and major barriers to the implementation of ICT. A descriptive methodology with a quantitative approach was used, applying surveys to fish-exporting companies. The study findings indicate that high acquisition costs, organizational culture, and difficulty in using ICTs due to lack of training and knowledge are the primary barriers to the adoption of ICTs. In contrast, the benefits of ICT implementation include inventory turnover, cost and delivery time reduction, supply chain control, and increased international negotiations. The study also highlights that the usefulness of ICTs varies depending on the area of application. For example, in sales and customer services ICTs can improve commercial strategies and enhance customer satisfaction by delivering orders within agreed timeframes. In warehousing, ICTs can reduce idle time, increase stock flow, and prevent stock-outs. In finance, they can assist with budget analysis, cost organization, and access to statistical charts.